TELAAH SINGKAT STRUKTUR DAN DESAIN ORGANISASI PERANGKAT PEMERINTAHAN NASIONAL PASCA PEMILU 2009 - Idup Suhady (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
The design and structure of government organization become very important in picturing sorts of needed government institutions, their roles and responsibilities, authorities, and interaction among institutions. They also function as a formalinstrument for implementing public policy within the state. Therefore, a review on government organization design and structure in this context is considered very crucial. The writer recognizes the fact that design and structure of government organization cannot be apart from certain political interest in the name of people’s will. The members of Ministerial Board formed by the elected president of General Election 2009 stem from political parties or a group of political parties backing the candidates of president and vice president. Without disregarding the important dimension of political interest, this writing focuses more on the view point of public administration. This review employs Law No 39 Year 2008 and Presidential Regulation No 47 Year 2009 about State Ministry as the main formal-normative reference.